Topical Insulin: A Game Changer for Non-Healing Leprosy Ulcers – A Case Series - Ratnaparkhi, Aniket; Fale, Purvesh; Rahangdale, Vishwas; Unni, Mahesh (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Leprosy, caused by Mycobacterium leprae, frequently leads to neuropathic trophic ulcers and ulcerative lesions associated with type II lepra reactions. These ulcers are difficult to treat due to sensory loss, repeated trauma, and poor vascularity, often responding inadequately to conventional therapies. Topical insulin has recently gained attention for its potential to enhance local wound healing by stimulating angiogenesis, collagen deposition, and re-epithelialization without systemic adverse effects. This case series included five male patients with Hansen’s disease who presented with chronic trophic ulcers or ulcerative lesions of lepra reaction. A solution of 0.1 ml Actrapid insulin diluted with 0.9 ml normal saline was irrigated directly to the ulcer surface twice daily and covered with sterile gauze for five minutes. The intervention was continued for four to six weeks. Ulcer size, depth, tissue quality, and granulation were assessed clinically and documented photographically at baseline and follow-up. All patients showed significant improvement within two weeks, with marked reduction in ulcer dimensions and healthy granulation tissue formation. Complete epithelization was achieved in four to six weeks. No local or systemic adverse effects were observed, and compliance was excellent. Topical insulin is a safe, economical, and effective therapeutic option for leprosy-associated ulcers, meriting further evaluation in larger controlled studies.